Pengaruh Sistem Pengendalian Internal, Sistem Informasi Akuntansi, dan Motivasi Kerja Terhadap Kinerja Karyawan pada Organisasi Perangkat Daerah Kota Malang - Azzaroh, Aviyanti Deah; Amin, Moh.; Sari, Arista Fauzi Kartika (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The current research has the objective of knowing the effect of internal control systems, accounting information systems and work motivation on employee performance. The population or respondents taken in this study were employees of all OPD (Regional Apparatus Organizations) in Malang City. The sampling technique in this study was carried out by purposive sampling. A total of 40 respondents with some specific criteria. The data source used is using primary data collected through questionnaires and using a Likert scale model. The results of this study are The influence of the Internal Control System, Accounting Information Systems and Work Motivation have a simultaneous effect on Employee Performance. Internal Control System and Accounting Information System Variables have a significant effect on Employee Performance. Work Motivation Variable has no significant effect on Employee Performance.Keywords: Internal control system; accounting information system; work motivation; employee performance.